Análisis de la brecha de veracidad en función del uso inadecuado del crédito tributario del impuesto a la renta en las personas jurídicas de la zona 3 del servicio de rentas internas - Miranda Solís, Alex Oswaldo (2017)
Tax credit use in the tax to the revenue returns about legal persons at the moment has not been verified by the Ecuadorian Taxes Administration, so it is not known what the amount is that the State has left to perceive when the taxpayers use that values to deduct yours tributes. So this investigation job analyze all tax credits use by the taxpayers and his incident in the gap of veracity the Tax to the Revenue. It has been considered to be the study of this topic in order proposed a plan of crossings of information that has been used as a part of taxes administration controls, who helps to identify tributary breaches that concern the tributary collection, the gap of veracity, besides the fact that it contributes as tool of persuasion in order that the contributor of gradual form expire voluntarily with his tax debts.